Performance of the Zamin District in the "Five Initiatives" Sports Competitions (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study examines the performance of the Zamin District in the "Five Initiatives" sports competitions, highlighting participation rates, achievements, and community impact. Utilizing a mixed-methods approach, data were collected through surveys, interviews, and performance metrics, revealing that 75% of respondents felt motivated to engage in sports. The district secured 15 medals, particularly excelling in athletics and team sports. While successes were noted, challenges such as inadequate infrastructure and funding constraints were identified. The findings underscore the importance of continued investment in sports development to enhance athletic performance and promote healthier lifestyles within the community.